Effects of Selenium- and Zinc-Enriched Lactobacillus plantarum SeZi on Antioxidant Capacities and Gut Microbiome in an ICR Mouse Model - Sini Kang; Rui Li; Hui Jin; Hyun Ju You; Geun Eog Ji (MDPI AG, 2020)
Selenium and zinc are essential trace minerals for humans with various biological functions. In this study, selenium- and zinc-tolerant lactic acid bacteria (LAB) isolates were screened out from human fecal samples. Amongst three hundred LAB isolates, the Lactobacillus plantarum SeZi strain displayed the tolerance against selenium and zinc with the greatest biomass production and bioaccumulation of selenium and zinc. To further assess the characteristics of this strain, the lyophilized L. plantarum SeZi were prepared and administered to Institute of Cancer Research (ICR) mice. The mice were divided into four groups, provided with normal chow (Con), or normal chow supplemented with Na2SeO3 and ZnSO4∙7H2O (SZ), L. plantarum SeZi (Lp), or selenium- and zinc-enriched L. plantarum SeZi (SZ + Lp), respectively. After 4 weeks of oral administration, the concentrations of selenium and zinc in blood were significantly increased in the SZ + Lp group when compared to the control or SZ group (p < 0.05). The increased selenium level led to an enhanced glutathione peroxidase activity and decreased blood malondialdehyde level in the SZ + Lp group (p < 0.05). Meanwhile, the results of bacterial community and microbial metabolic pathway analysis via 16S rRNA gene amplicon sequencing showed that L. plantarum SeZi significantly promoted the utilization of selenocysteine, seleno-cystathionine and seleno-methionine in the selenocompounds metabolism. Here, the in vivo antioxidant capacities of the selenium- and zinc-enriched lactobacillus strain showed us the utilization of a unique probiotic as a Se/Zn supplement with high availability, low toxicity, and additional probiotic advantages.